2013
DOI: 10.1002/jbm.a.34718
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite‐coated magnesium implants with improved in vitro and in vivo biocorrosion, biocompatibility, and bone response

Abstract: Magnesium and its alloys are candidate materials for biodegradable implants; however, excessively rapid corrosion behavior restricts their practical uses in biological systems. For such applications, surface modification is essential, and the use of anticorrosion coatings is considered as a promising avenue. In this study, we coated Mg with hydroxyapatite (HA) in an aqueous solution containing calcium and phosphate sources to improve its in vitro and in vivo biocorrosion resistance, biocompatibility and bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 51 publications
1
57
2
1
Order By: Relevance
“…With impurities as well as alloying or coating elements, it is important to keep in mind the tolerable upper intake levels of these elements in humans so that improved strength or corrosion resistance does not come at the expense of biocompatibility. Pure Mg alloys for biomedical applications have mostly been replaced by other alloys, though some studies still contain pure magnesium, often as a control [102][103][104][105].…”
Section: Biocompatibilitymentioning
confidence: 99%
“…With impurities as well as alloying or coating elements, it is important to keep in mind the tolerable upper intake levels of these elements in humans so that improved strength or corrosion resistance does not come at the expense of biocompatibility. Pure Mg alloys for biomedical applications have mostly been replaced by other alloys, though some studies still contain pure magnesium, often as a control [102][103][104][105].…”
Section: Biocompatibilitymentioning
confidence: 99%
“…The HA coated magnesium substrate showed enhanced corrosion resistance in simulated body fluid [21]. Moreover, the HA coated magnesium samples showed enhanced cytocompatibility and mitigated the in vivo biodegradation of magnesium implant, particularly over the first 6 weeks of implantation, which considerably promoted bone growth at the interface between the implant and bone [22]. However, the fabrication of HA layer by this method on other substrates, such as PEO coating, has been rarely investigated [23].…”
Section: Introductionmentioning
confidence: 89%
“…Calcium phosphate precipitation improved the protectiveness of the coatings; therefore the mass-transfer conditions of the test solution should be controlled, depending on the targeted part of the body. It has been reported that corrosion of uncoated Mg alloys in bone marrow is faster than that in cortical bone and soft tissue [20,39,40]. Kim et al reported that HAp coating prevented corrosion of pure Mg in the bone marrow of rabbit tibias, although calcium phosphate precipitation behaviour on the HAp coating in bone marrow was not examined [20].…”
Section: Effects Of the Mass-transfer Conditionsmentioning
confidence: 98%
“…The HAp coating showed good adhesiveness to the Mg alloy substrate under static tensile deformation with 5% elongation and under fatigue loading accompanying 3% cyclic elongation [18]. Kim et al reported that a similar HAp coating on pure Mg gave good corrosion protectiveness, biocompatibility, and bone response in the bone-pericranium pouches of rats and/or in tibial shafts of rabbits [20]. A brushite (dicalcium phosphate dihydrate) coating prolonged the in vivo degradation period of a Mg-Nd-Zn-Zr alloy [21].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation